Perspectives of Ontario School Board Administrators on Fostering Plurilingualism in Secondary Level International Languages Classrooms - Granger, Lesya Alexandra (Université d'Ottawa / University of Ottawa, 2021)
Abstract This study examines Continuing Education (ContEd) administrators’ understanding of the notion of plurilingualism (PL) and its application in the context of Grade 9 to 12 International Languages (IL) classrooms in Ontario. Through cross-case analysis and a phenomenological lens, the perspectives of 17 administrators from across Ontario were analyzed in reference to PL as it is elaborated in the CEFR and the 2016 IL curriculum. Participants expressed a need for administrators to learn about PL-inspired classroom practices in order to guide and train IL teachers, to foster innovation in the immersion context of IL classrooms, and to advocate for IL and PL in the broader school system. The implications are far-reaching and touch on professional development for IL administrators and teachers, student motivation, and discursive practices in IL and the broader school system. The study contributes to theory on PL, SLE research about PL in the IL context, and administrators in the ContEd context.
Keywords: plurilingualism; international languages; Ontario school board administrators; multilingualism; heritage languages; continuing education; Common European Framework of Reference for Languages; CEFR